An Investigation of Feasibility and Safety of Bi‐Modal Stimulation for the Treatment of Tinnitus: An Open‐Label Pilot Study. Issue 8 (16th June 2016) - Hamilton, Caroline; D'Arcy, Shona; Pearlmutter, Barak A.; Crispino, Gloria; Lalor, Edmund C.; Conlon, Brendan J.
Abstract : Objectives: Tinnitus is the perception of sound in the absence of an external auditory stimulus. It is widely believed that tinnitus, in patients with associated hearing loss, is a neurological phenomenon primarily affecting the central auditory structures. However, there is growing evidence for the involvement of the somatosensory system in this form of tinnitus. For this reason it has been suggested that the condition may be amenable to bi‐modal stimulation of the auditory and somatosensory systems. We conducted a pilot study to investigate the feasibility and safety of a device that delivers simultaneous auditory and somatosensory stimulation to treat the symptoms of chronic tinnitus. Methods: A cohort of 54 patients used the stimulation device for 10 weeks. Auditory stimulation was delivered via headphones and somatosensory stimulation was delivered via electrical stimulation of the tongue. Patient usage, logged by the device, was used to classify patients as compliant or noncompliant. Safety was assessed by reported adverse events and changes in tinnitus outcome measures. Response to treatment was assessed using tinnitus outcome measures: Minimum Masking Level (MML), Tinnitus Loudness Matching (TLM), and Tinnitus Handicap Inventory (THI). Results: The device was well tolerated by patients and no adverse events or serious difficulties using the device were reported. Overall, 68% of patients met the defined compliance threshold. Compliant patients ( N = 30) demonstrated statistically significant improvements in mean outcome measures after 10 weeks of treatment: THI (−11.7 pts, p < 0.001), TLM (−7.5dB, p < 0.001), and MML (−9.7dB, p < 0.001). The noncompliant group ( N = 14) demonstrated no statistical improvements. Conclusion: This study demonstrates the feasibility and safety of a new bi‐modal stimulation device and supports the potential efficacy of this new treatment for tinnitus.